RESEARCH OF A SIMULATION MODEL OF A SELF-ORGANIZING VIRTUAL PRIVATE COMMUNICATION NETWORK. - Sadchikova Svetlana Aleksandrovna; Abdurasulov Zohirjon Komiljon Ugli (The latest pedagogical and psychological innovations in education, 2025)
A simulation model of a self-organizing virtual private communication network (SOVPCN) based on secure peer-to-peer communication, adaptive topology management, and decentralized routing is shown in this study. In order to guarantee communication dependability without centralized supervision, the work investigates strategies of autonomous resource distribution, node coordination, and encrypted traffic exchange. Improvements in network scalability, failure tolerance, and defense against external threats are demonstrated by the suggested simulation. The findings demonstrate that self-organizing principles can greatly improve virtual private communication systems' security and efficiency, making them appropriate for dispersed infrastructures of the future.